Centering justice: Transforming paradigms of approach, design and implementation. Issue 2 (3rd April 2019) - Jumarali, Selima N.; Mandiyan, Dee; Javdani, Shabnam
Abstract: This concluding article presents visions for future research, prevention, intervention, and policy. This paper positions existing research paradigms against social justice principles, problematizing the ideological underpinnings of the legal system and its disproportionate impact on oppressed groups, including through the persistent overrepresentation of youth of color and/or marginalized genders. Highlighting the areas of challenge suggested by each of the manuscripts within the themed issue, this paper encourages critical shifts in the approach, design, and implementation of work with system-involved youth. Recommendations include: strengths-based, rights-based, systems accountability frameworks that account for structural forces and societal issues that produce oppressive contexts, amending and re-defining language to de-stigmatize youth, shifting the targets of this work up the power gradient to avoid victim blaming of youth, engaging participatory methods that provide direct benefit to youth, and critical discourse analysis alongside individual reflexivity to keep ourselves accountable in this work.